Aluminum ion battery
By growing the composite material of cobalt disulfide nanoparticles in situ on the surface of carbon fibers as the positive electrode of aluminum ion batteries, the problem of poor circulation performance of existing aluminum ion batteries in industrial production is solved, and higher circulation stability and safety performance are achieved .
Patent Information
- Application Number
- CN202411603633.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-07
AI Technical Summary
In industrial production, existing aluminum ion batteries face problems such as lack of positive electrode materials and side reactions between adhesives and electrolytes, resulting in poor circulation performance.
CoS2@CNFs, a nanoparticle composite material grown in situ on the carbon fiber surface, was used as the positive electrode, and an aluminum sheet was used as the negative electrode, and an electrolyte prepared by anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride were used. , the composite material was prepared by electrospinning and heat treatment process.
It improves the cycle stability of aluminum ion batteries, avoids side reactions of electrolytes and adhesives, reduces production costs, reduces the weight of the battery itself, and provides safe charging and discharging capabilities under high current conditions.
Smart Images

Figure CN119400839A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of aluminum ion batteries, and in particular to a rechargeable aluminum ion battery. Background Art
[0002] Lithium-ion batteries are facing safety issues such as limited lithium resource supply and flammability and explosion. Therefore, it is very necessary to develop a new secondary battery system that is safe and low-cost. Aluminum-ion batteries based on aluminum negative electrodes have a theoretical storage capacity of about four times that of lithium ions due to their three-electron transfer redox reaction; in addition, aluminum is the most abundant metal on earth, its price is much lower than lithium, and aluminum secondary batteries based on chloroaluminate ionic liquid electrolytes will not spontaneously combust, which greatly improves the safety of the battery. Therefore, aluminum-ion batteries are expected to replace lithium-ion batteries and become the mainstream batteries for large-scale energy storage systems.
[0003] At present, there have been many studies on aluminum ion batteries, such as patent number 202410454283.0, the patent name is a graphene-modified carbon fiber-aluminum structure energy storage integrated composite material that can be quickly charged and discharged and its preparation method. It is a porous resin as the matrix, carbon fiber graphene electrode as the positive electrode, reinforcing material and aluminum mesh as the negative electrode, and graphene as the active substance. It effectively improves the problems of slow charging and unstable cycle of traditional aluminum ion graphite electrodes during the charging and discharging process; such as patent number 202410321419.0, the name is a modified carbon nanofiber composite material and its preparation method and application. The modified carbon nanofiber composite material is obtained by a hydrothermal method and used as the positive electrode of the aluminum ion battery to improve the specific capacity and cycle stability of the aluminum ion battery.
[0004] However, the current industrial production of aluminum-ion batteries still faces many challenges, such as the lack of suitable positive electrode materials, side reactions between adhesives and electrolytes, etc., which lead to poor battery cycle performance. Summary of the invention
[0005] Based on the above description, the present invention proposes an aluminum ion battery, in which a cobalt disulfide nanoparticle composite material CoS2@CNFs grown in situ on the surface of carbon fiber is used as a positive electrode, an aluminum sheet is used as a negative electrode, a diaphragm is a Whatman glass fiber diaphragm, and an electrolyte is prepared by anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride in a molar ratio of 1.3:1, thereby improving the cycle stability of the battery.
[0006] The technical solution adopted is: an aluminum ion battery, including a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode is assembled from aluminum sheets, the positive electrode is a cobalt disulfide / carbon micro-nano fiber composite material, the separator is Whatman, and the electrolyte is prepared from anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride in a molar ratio of 1.3:1.
[0007] The preparation method of cobalt disulfide / carbon micro-nano fiber composite material comprises the following steps: 1) Cobalt acetate, N,N-dimethylformamide and polyacrylonitrile are mixed to obtain an electrospinning precursor; 2) electrospinning the electrospinning precursor obtained in step 1) to obtain fibers; 3) pretreating the fiber obtained in step 2) in air; 4) reducing the pretreated fibers in step 3) to Co@CNFs at high temperature; 5) mixing the Co@CNFs obtained in step 4) with sublimed sulfur and subjecting them to molten sulfur treatment to form a Co@CNFs / S mixture; 6) calcining the Co@CNFs / S mixture obtained in step 5) to obtain a cobalt disulfide / carbon micro-nano fiber composite material CoS2@CNFs.
[0008] The mass content of cobalt disulfide in the prepared cobalt disulfide / carbon micro-nano fiber composite material CoS2@CNFs is 50%, and the size of cobalt disulfide is 30nm.
[0009] Furthermore, in step 1), 2 g of cobalt acetate, 30 ml of N,N-dimethylformamide, and 3 g of polyacrylonitrile are mixed and stirred to obtain a clear and uniform mixed solution to obtain an electrospinning precursor.
[0010] Furthermore, in step 2), the parameters of electrospinning include: voltage of 15 kV, distance between needle and collector of 18 cm, and propulsion speed of 0.06 ml / min.
[0011] Furthermore, the pretreatment in step 3) is to heat the fiber prepared in step 2) from room temperature to 280°C, with a heating rate of 1°C / min and a heat treatment time of 2h.
[0012] Furthermore, the high temperature reduction in step 4) is to reduce the fiber pretreated in step 3) from high temperature to room temperature and then to 900°C, with a heating rate of 5°C / min and a heat treatment time of 2h.
[0013] Furthermore, in the molten sulfur treatment in step 5), the mass ratio of the Co@CNFs obtained in step 4) to sulfur powder is 4:1, and the heat treatment temperature is 155°C.
[0014] The present invention uses an electrostatic spinning method and a heat treatment process to in-situ grow uniformly sized and evenly distributed cobalt disulfide nanoparticles on the surface of carbon fibers. The obtained cobalt disulfide / carbon micro-nano fibers are used as the positive electrode of aluminum ion batteries. Compared with the prior art, the advantages of the present invention are: 1) Cobalt disulfide / carbon micro-nano fiber as a binder-free electrode avoids the side reaction between electrolyte and binder in aluminum ion batteries, and can improve the cycle stability of aluminum batteries; 2) The prepared positive electrode material does not require adhesives and conductive agents, which reduces the production cost of aluminum ion batteries and also reduces the weight of the battery itself; 3) The cobalt disulfide / carbon micro-nano fiber electrode material uses carbon fiber as a support substrate, which alleviates the destruction of the electrode structure during the cycle; 4) Cobalt disulfide nanoparticles are evenly distributed on the fiber surface to form a three-dimensional conductive network structure, which increases the reaction interface and shortens the kinetic barrier of ion transport. It can be charged and discharged under high current conditions, providing feasibility for aluminum ion batteries with good safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the XRD pattern of the CoS2@CNFs three-dimensional network composite material synthesized in Example 1; Figure 2 This is a desorption curve diagram of the CoS2@CNFs three-dimensional network composite material synthesized in Example 1; Figure 3 This is the electron energy spectrum of the XPS full spectrum elemental analysis of the CoS2@CNFs three-dimensional network composite material synthesized in Example 1; Figure 4 This is a scanning electron microscope image (SEM) of the CoS2@CNFs three-dimensional network composite material synthesized in Example 1; Figure 5 The CoS2@CNFs three-dimensional network composite material synthesized in Example 1 was used as an electrode at 500 mA g -1 Battery cycling performance diagram at different current densities. DETAILED DESCRIPTION
[0016] The present invention will be further described in detail below with reference to the accompanying drawings and by way of examples. The following examples are intended to explain the present invention but the present invention is not limited to the following examples.
[0017] Example 1: See Figures 1 to 5 As shown, an aluminum ion battery includes a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode is assembled from aluminum sheets, the positive electrode is a cobalt disulfide / carbon micro-nano fiber composite material, the separator is a whatman glass fiber separator, and the electrolyte is prepared by anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride in a molar ratio of 1.3:1; the cobalt disulfide / carbon micro-nano fiber composite material as the positive electrode has a specific surface area of 123.63 m 2 g -1 , the diameter of the fiber is 500nm and the diameter of cobalt disulfide is 30nm.
[0018] The preparation method of cobalt disulfide / carbon micro-nano fiber composite material comprises the following steps: 1) Dissolve 2 g of cobalt acetate and 3 g of polyacrylonitrile in 30 ml of N,N-dimethylformamide and stir until a clear and uniform mixed solution is obtained to obtain an electrospinning precursor; 2) electrospinning the electrospinning precursor obtained in step 1) with the following parameters: voltage of 15 kV, distance between needle and collector of 18 cm, propulsion speed of 0.06 ml / min, to obtain fibers; 3) pre-treating the fiber obtained in step 2) in air at room temperature to 280°C, at a heating rate of 1°C / min, and for 2 hours; 4) The fibers pretreated in step 3) were reduced to Co@CNFs by high temperature, with the temperature rising from room temperature to 900°C, the heating rate being 5°C / min, and the heat treatment time being 2h; 5) heat treating the Co@CNFs and sulfur powder obtained in step 4) at a mass ratio of 4:1 at 155°C for 12h to form a Co@CNFs / S mixture; 6) The Co@CNFs / S mixture obtained in step 5) was heat treated at 450°C for 4 hours at a heating rate of 2°C / min to obtain a cobalt disulfide / carbon micro-nano fiber composite material (CoS2@CNFs), that is, cobalt disulfide nanoparticles were in situ grown on the surface of the carbon fiber.
[0019] The mass content of cobalt disulfide in the prepared cobalt disulfide / carbon micro-nano fiber composite material CoS2@CNFs is 50%, the diameter of cobalt disulfide is 30nm, and the fiber diameter is 500nm.
[0020] The crystal structure of the cobalt disulfide / carbon micro-nano fiber composite material prepared in Example 1 was determined by X-ray diffractometer (XRD). Figure 1 As shown, the XRD spectrum shows that several characteristic peaks of the cobalt disulfide / carbon micro-nano fiber composite material match the characterization card (JCPDS No. 41-1471), indicating that CoS2 is the main phase. Figure 2 The N2 desorption isotherm of the cobalt disulfide / carbon nanofiber composite prepared in Example 1 is used to analyze the pore structure of the CoS2@CNFs composite. The results show that the BET specific surface area of CoS2@CNFs is 13.42 and 123.63 m 2 g -1 . Figure 3 The electron energy spectrum of the full spectrum elements of the cobalt disulfide / carbon micro-nano fiber composite material prepared in Example 1 is shown in the XPS analysis. Figure 3 It can be seen that the prepared samples are mainly composed of C, Co and S elements. Figure 4This is a SEM image of the cobalt disulfide / carbon micro-nano fiber composite material prepared in Example 1, which shows that the cobalt disulfide nanoparticles can be evenly distributed on the surface of the carbon fiber, the diameter of the cobalt disulfide nanoparticles is 30nm, and the morphology is uniform. In addition, the cobalt disulfide / carbon micro-nano fiber composite material continuously and uniformly forms a three-dimensional network, and the fiber diameter is 500nm.
[0021] Embodiment 2: An aluminum ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode is assembled from aluminum sheets, the positive electrode is a cobalt disulfide / carbon micro-nano fiber composite material, the separator is a Whatman glass fiber separator, and the electrolyte is prepared by anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride in a molar ratio of 1.3:1; in the preparation of the cobalt disulfide / carbon micro-nano fiber composite material, pure carbon fiber is first prepared, and the steps are as follows: 1) Take 3g of polyacrylonitrile, dissolve it in 27ml of N,N-dimethylformamide, and stir until the mixed solution is clear and uniform; 2) The mixed solution in step 1) was subjected to electrospinning, and the parameters were: voltage of 15 kV, distance between the needle and the collector of 18 cm, and propulsion speed of 0.06 ml / min; 3) pre-treating the fibers spun in step 2) by heating the temperature from room temperature to 280°C at a heating rate of 1°C / min for 2 hours; 4) Carbonizing the fibers pretreated in step 3) under the conditions of heating from room temperature to 900°C, heating rate of 5°C / min, heat treatment time of 2h, and obtaining pure carbon fibers; 5) Take 4 mmol of sodium thiosulfate and 4 mmol of cobalt acetate, dissolve them in 80 ml of deionized water respectively, and stir until completely dissolved; 6) Put the pure carbon fiber prepared in step 4) into the solution obtained in step 5) and perform hydrothermal reaction at 180°C for 24 hours; 7) The product obtained in step 6) is washed with deionized water and alcohol, and dried in a vacuum drying oven at 60° C. to obtain a carbon fiber-supported cobalt disulfide composite material (CoS2 / CNFs).
[0022] The carbon fiber-supported cobalt disulfide composite material (CoS2 / CNFs) obtained in Example 2 was directly used as the positive electrode active material of the aluminum ion battery. -1 The battery was tested at a current density of 68 mAh g after 200 cycles. -1 .
[0023] Embodiment 3: An aluminum ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode is assembled from aluminum sheets, the positive electrode is a cobalt disulfide / carbon micro-nano fiber composite material, the separator is a Whatman glass fiber separator, and the electrolyte is prepared by anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride in a molar ratio of 1.3:1; wherein the preparation method of the cobalt disulfide / carbon micro-nano fiber composite material comprises the following steps: 1) Take 4 mmol of sodium thiosulfate and 4 mmol of cobalt acetate, dissolve them in 80 ml of deionized water respectively, and stir until completely dissolved; 2) subjecting the solution obtained in step 1) to a hydrothermal reaction at 180°C for 24 hours; 3) The product obtained in step 2) is washed with deionized water and alcohol, and dried in a vacuum drying oven at 60° C. to obtain black cobalt disulfide powder.
[0024] 4) adding the cobalt disulfide obtained in step 3) into polyacrylonitrile and stirring for 12 hours; 5) The mixed solution obtained in step 4) was subjected to electrospinning, and the parameters were: voltage of 15 kV, distance between the needle and the collector of 18 cm, and propulsion speed of 0.06 ml / min; 6) pre-treating the fibers spun in step 5) by heating the room temperature to 280°C at a heating rate of 1°C / min for 2 hours; 7) The fiber pretreated in step 6) is heat treated at room temperature to 450°C, at a heating rate of 2°C / min, and for 4 hours. The obtained product is a carbon fiber-coated cobalt disulfide composite material.
[0025] The carbon fiber-coated cobalt disulfide composite material obtained in Example 3 was directly used as the positive electrode active material of the aluminum ion battery. The separator was Whatman, the electrolyte was prepared by anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride in a ratio of 1.3:1, and the negative electrode was assembled into a soft-pack battery with aluminum sheets. -1 The battery was tested at a current density of 63 mAh g after 200 cycles. -1 .
[0026] 1) Take 2g of cobalt acetate and 3g of polyacrylonitrile, dissolve them in 30ml of N,N-dimethylformamide, and stir until the mixed solution is clear and uniform; 2) The mixed solution in step 1) was subjected to electrospinning, and the parameters were: voltage of 15 kV, distance between the needle and the collector of 18 cm, and propulsion speed of 0.06 ml / min; 3) pre-treating the fibers spun in step 2) by heating the temperature from room temperature to 280°C at a heating rate of 1°C / min for 2 hours; 4) The fibers pretreated in step 3) were subjected to high temperature reduction to form Co@CNFs, with the temperature rising from room temperature to 900°C, the heating rate being 5°C / min, and the heat treatment time being 2h; 5) The Co@CNFs and sulfur powder obtained by high temperature reduction in step 4) were heat treated at 155°C for 12 h in a mass ratio of 4:1; 6) The Co@CNFs / S mixed product heat-treated in step 5) was heat-treated at 450°C for 1 h at a heating rate of 2°C / min to obtain in-situ grown cobalt disulfide nanoparticles (CoS2@CNFs) on the carbon fiber surface.
[0027] 1) Take 2g of cobalt acetate and 3g of polyacrylonitrile, dissolve them in 30ml of N,N-dimethylformamide, and stir until the mixed solution is clear and uniform; 2) The mixed solution in step 1) was subjected to electrospinning, and the parameters were: voltage of 15 kV, distance between the needle and the collector of 18 cm, and propulsion speed of 0.06 ml / min; 3) pre-treating the fibers spun in step 2) by heating the temperature from room temperature to 280°C at a heating rate of 1°C / min for 2 hours; 4) The fibers pretreated in step 3) were subjected to high temperature reduction to form Co@CNFs, with the temperature rising from room temperature to 900°C, the heating rate being 5°C / min, and the heat treatment time being 2h; 5) The Co@CNFs and sulfur powder obtained by high temperature reduction in step 4) were heat treated at 155°C for 12 h in a mass ratio of 4:1; 6) The Co@CNFs / S mixed product heat-treated in step 5) was heat-treated at 450°C for 8 hours with a heating rate of 2°C / min to obtain in-situ grown cobalt disulfide nanoparticles (CoS2@CNFs) on the carbon fiber surface.
[0028] Comparative Example 6: 1) Take 4 mmol of sodium thiosulfate and 4 mmol of cobalt acetate, dissolve them in 80 ml of deionized water respectively, and stir until completely dissolved; 2) subjecting the solution obtained in step 1) to a hydrothermal reaction at 180°C for 24 hours; 3) washing the product obtained in step 2) with deionized water and alcohol, and drying it in a vacuum drying oven at 60° C. to obtain black cobalt disulfide powder; 4) PTFE, conductive carbon and cobalt disulfide prepared in step 3) are mixed in a mass ratio of 7:2:1, ground in an alcohol solution, and then the mixed material is processed by a roller press, and finally cut into discs by a mechanical cutter to serve as the aluminum ion positive electrode. The diaphragm is whatman, the electrolyte is prepared by anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride in a ratio of 1.3:1, and the negative electrode is an aluminum sheet assembled into a soft-pack battery.
[0029] The product obtained in this example is used as the positive electrode material of aluminum ion battery at 200mA g -1 The battery was tested at a current density of 500 cycles and its discharge capacity was 55 mAh g -1 .
Claims
1. An aluminum ion battery, characterized in that: It includes a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode is assembled from aluminum sheets, the positive electrode is a cobalt disulfide / carbon micro-nano fiber composite material, the separator is Whatman, and the electrolyte is prepared from anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride in a molar ratio of 1.3:
1.
2. An aluminum ion battery according to claim 1, characterized in that The preparation method of the cobalt disulfide / carbon micro-nano fiber composite material comprises the following steps: 1) Cobalt acetate, N,N-dimethylformamide and polyacrylonitrile are mixed to obtain an electrospinning precursor; 2) electrospinning the electrospinning precursor obtained in step 1) to obtain fibers; 3) pretreating the fiber obtained in step 2) in air; 4) reducing the pretreated fibers in step 3) to Co@CNFs at high temperature; 5) mixing the Co@CNFs obtained in step 4) with sublimed sulfur and subjecting them to molten sulfur treatment to form a Co@CNFs / S mixture; 6) calcining the Co@CNFs / S mixture obtained in step 5) to obtain a cobalt disulfide / carbon micro-nano fiber composite material CoS2@CNFs.
3. An aluminum ion battery according to claim 1 or 2, characterized in that The cobalt disulfide / carbon micro-nano fiber composite material CoS2@CNFs has a diameter of 500 nm; the mass content of cobalt disulfide is 50%, the diameter of cobalt disulfide is 30 nm, and the specific surface area of the cobalt disulfide / carbon micro-nano fiber composite material is 123.63 m 2 g -1 .
4. An aluminum ion battery according to claim 2, characterized in that In the step 1), 2 g of cobalt acetate, 30 ml of N,N-dimethylformamide and 3 g of polyacrylonitrile are mixed and stirred to obtain a clear and uniform mixed solution to obtain an electrospinning precursor.
5. An aluminum ion battery according to claim 2, characterized in that In the step 2), the electrospinning parameters include: voltage of 15 kV, distance between the needle and the collector of 18 cm, and propulsion speed of 0.06 ml / min.
6. An aluminum ion battery according to claim 2, characterized in that In the step 3), the pretreatment is to heat the temperature from room temperature to 280°C, the heating rate is 1°C / min, and the heat treatment time is 2h.
7. An aluminum ion battery according to claim 2, characterized in that In the step 4), the high temperature reduction is carried out from room temperature to 900° C., the heating rate is 5° C. / min, and the heat treatment time is 2 h.
8. An aluminum ion battery according to claim 2, characterized in that In the step 5) molten sulfur treatment, the mass ratio of Co@CNFs and sulfur powder is 4:1, and the heat treatment temperature is 155°C.
Citation Information
Patent Citations
Modified carbon nanofiber composite material as well as preparation method and application thereof
CN118016858A
Graphene modified carbon fiber-aluminum structure energy storage integrated composite material capable of being charged and discharged rapidly and preparation method of graphene modified carbon fiber-aluminum structure energy storage integrated composite material
CN118336083A